Lithium activated enhancement in UV-photo response of europium doped ZnO thin film - kumar P.; Chauhan V.; Singh R.; Pandey P.C. (My University, 2025)
The advancement in material functionality is an important tool to enhance the sensitivity of ZnO-based UV detectors. The ZnO-based UV detector with different morphology has shown interesting results but the improvement is limited. The incorporation of dopant not only gives the characteristic property of dopant but also tunes electron, hole, and defect concentrations. This work has shown significant improvement in the performance of ZnO-based UV detector with the incorporation of Eu1% and Li1% as the dopants. Sol-gel derived ZnO and Eu 1% doped ZnO (Eu1) and Eu1% Li1% doped ZnO thin film (Eu1Li1) have been investigated for UV detector application. The HRXRD and AFM confirm the high crystalline quality with granular structure in all deposited thin films. The enhanced UV absorption in doped thin film confirms the potentiality of Eu1Li1 thin film as a UV detector. The observed photocurrent value increases twice in Eu1%Li1% doped ZnO thin film (6.75 μA) as compared to pure ZnO (3.14 μA) at 4.0 V bias voltage under UV irradiation of wavelength 325 nm. The responsivity of the Eu1Li1 UV detector is twice as compared to pure ZnO. The enhanced photocurrent is due to an increase of favorable oxygen defect concentration arising with Eu1% and Li1% substitution. © 2022 Elsevier B.V.